PHYTOCHEMISTRY SCREENING AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF BIOACTIVE COMPOUNDS PRESENT IN KARO TRADITIONAL OIL, AN INDONESIAN TRADITIONAL HERBAL MEDICINE - PRIMADINA, NOVA; BASORI, ACHMAD; S PERDANAKUSUMA, DAVID (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The purpose of this research was to observe the bioactive compounds of Karo traditional oil by phytochemistry screening and gas chromatography-mass spectrometry (GC-MS) analysis. Alkaloid, Results: Terpenoid and flavonoid compounds were found, and no polyphenol compound from phytochemistry screening and 16 constituents were identified from the GC-MS analysis, α-pinene was found as the major component (74.47%), delta-3-carene (9.62%), 1% of octane, dodecane, camphor, undecane, isodecane, sabinene, hexadecane, nonane, and <1% tridecane, cyclohexane, pentacosane, heptadecan, limonene, and camphene. Conclusion: Karo traditional oil works as a potent anti-inflammation at the inflammation phase of the wound healing process by suppressing the pro-inflammatory cytokines and promote anti-inflammatory cytokines.